PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 011 REDANG SEKO KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Nur Pitri Rahma; Eddy Noviana; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to determine whether the application of cooperative model type Teams Games Tournaments (TGT) can improve civic education learning outcome students grade V of state elementary school 011 Redang Seko. The form of this research is Classroom Action Research (PTK) with subjects in class V which number 32 people. The problem of this study is the low student learning outcomes which are characterized by the large number of students under the KKM. Data collection techniques used were observation, tests, and interviews and then analyzed using quantitative descriptive analysis techniques. The results of the study concluded that Civic learning with the cooperative learning type TGT can improve teacher activities, student activities and learning outcomes of civic education. Seen in the first cycle of the first meeting the percentage of teacher activity scores was 70.83% to 83.33%. In the second cycle the first meeting the percentage of teacher activities obtained was 91.66%, then increased to 95.83%. The average percentage of student activity in the first cycle of the first meeting was 75% to 79.16%. In the second cycle the first meeting the percentage of student activities obtained was 83.33% then increased to 91.66%. The average student learning outcomes increased from the basic score of 65.71 to 77.03 in the first cycle and in the second cycle the average learning outcomes increased to 81.56. The increase in the average student learning outcomes from the basic score to the second cycle is 24.12%. It can be concluded that the cooperative learning model type TGT can improve the learning outcomes of grade V 011 Redang Seko elementary school in the district of Lirik, in the Indragiri Hulu Regency.Key Words: Cooperative Learning Model Type Teams Games Tournaments (TGT), Civic education learning outcomes.